2020
DOI: 10.1186/s12864-020-6649-2
|View full text |Cite
|
Sign up to set email alerts
|

Trend analysis of the role of circular RNA in goat skeletal muscle development

Abstract: Background: Circular RNA (circRNA) is produced during the splicing of mRNA (in addition to linear splicing) and is part of the gene regulatory network. The temporal expression patterns the different developmental stages were inseparable from these molecules' function. Results: Skeletal muscles of Anhui white goat (AWG) across seven fetal to postnatal development stages were sequenced and 21 RNA sequencing libraries were constructed. We thereby identified 9090 circRNAs and analyzed their molecular properties, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 49 publications
1
12
0
Order By: Relevance
“…Recently, Ling et al. (2020) performed analysis of circRNAs expression in AWG skeletal muscle development. A total of 9,090 circRNAs were identified from seven foetal to postnatal development stages.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, Ling et al. (2020) performed analysis of circRNAs expression in AWG skeletal muscle development. A total of 9,090 circRNAs were identified from seven foetal to postnatal development stages.…”
Section: Methodsmentioning
confidence: 99%
“…A study on goat skeletal muscle tissue reported that 92.4% of circRNAs originated from exonic regions, which indicates their regulatory role at the post-transcriptional level [75]. Furthermore, functional clustering of circRNAs showed their association with different important signaling pathways, such as Wnt/PI3K-Akt, which is essential for muscle development [75]. In Nile tilapia only 622 distinct circRNAs were present in fast muscle.…”
Section: Role Of Circrnas In Myogenesis and Growthmentioning
confidence: 99%
“…As we mentioned earlier, muscle development in livestock is a complex physiological process, and different kinds of circRNAs play different roles in muscle development. Ling et al (2020) find that cluster16 circRNAs are highly expressed in the early and late stages of muscle development of Anhui white goat (AWG) embryo and are directly involved in the Wnt signal pathway, AMPK signal pathway, and so on. It can be seen that circRNAs can directly regulate the muscle development of livestock.…”
Section: Circrnas Regulate Muscle Development Of Livestock Animalsmentioning
confidence: 99%